A concise flow synthesis of indole-3-carboxylic ester and its derivatisation to an auxin mimic - Baumann, Marcus; Baxendale, Ian R.; Deplante, Fabien (Beilstein Journal of Organic Chemistry, 2017)
An assembled suite of flow-based transformations have been used to rapidly scale-up the production of a novel auxin mimic-based herbicide which was required for preliminary field trials. The overall synthetic approach and optimisation studies are described along with a full description of the final reactor configurations employed for the synthesis as well as the downstream processing of the reaction streams.
Keywords: flow chemistry; heterocycle; hydrogenation; indole; multistep